2021
DOI: 10.1002/adsc.202001413
|View full text |Cite
|
Sign up to set email alerts
|

Acid‐Promoted Expeditious Syntheses of Aminated Dibenzosultams via Palladium/Norbornene Cooperatively Catalysed C−H Amination/Arylation

Abstract: Herein we reported a protocol to access aminated benzofused sultams through sequential ortho‐amination, followed by ipso‐arylation of aryl iodide bearing sulfonamide functional group via palladium/norbornene coorperative catalysis. This reaction has showcased a broad spectrum of substrate scope under mild conditions with moderate to good efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…After investigating the substrate scope, we decided to use our method for the synthesis of N-15 labelled cinnamonitrile 2* . After evaluating all commercially available N-15 labelled ammonium salts, we found that N-15 ammonium chloride 6 ( 15 NH 4 Cl; $169 per 1 g) and N-15 ammonium acetate 15 ( 15 NH 4 OAc; $491 per g) were the most favourable options, with cost considerations leading us to choose 15 NH 4 Cl. Extra base was essential in the current transformation with NH 4 Cl (see the ESI, page 20, Scheme S4-1†).…”
Section: Resultsmentioning
confidence: 99%
“…After investigating the substrate scope, we decided to use our method for the synthesis of N-15 labelled cinnamonitrile 2* . After evaluating all commercially available N-15 labelled ammonium salts, we found that N-15 ammonium chloride 6 ( 15 NH 4 Cl; $169 per 1 g) and N-15 ammonium acetate 15 ( 15 NH 4 OAc; $491 per g) were the most favourable options, with cost considerations leading us to choose 15 NH 4 Cl. Extra base was essential in the current transformation with NH 4 Cl (see the ESI, page 20, Scheme S4-1†).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the mechanism research of the above documents, , as well as our experimental results and DFT calculations, we propose a reasonable mechanism. First, o -iodotoluene and Pd(0) undergo oxidative addition to generate intermediate I , which is followed by insertion into norbornadiene and subsequent ortho -C–H activation.…”
mentioning
confidence: 81%
“…Subsequently, the strategy was further extended to the construction of allene-and sulfur-containing skeleton. 10…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A set of control experiments were subsequently conducted to understand the role of each component. The pivalate anion proved critical for this reaction, as the yield of 3a decreased dramatically either without pivalic acid or using Pd­(OAc) 2 instead of Pd­(OPiv) 2 as the catalyst (entries 2–3). Changing the cocatalyst N 1 * to 2-amide-substituted norbornene N 2 * led to no 3a formation, with large amounts of starting materials remaining, indicative of the importance of the ester group in N 1 * (entry 4).…”
mentioning
confidence: 99%